Evaluation of takayasu arteritis with delayed contrast-enhanced MR imaging by a free-breathing 3D IR turbo FLASH. Issue 51 (December 2017) - Liu, Min; Liu, Weifang; Li, Haoyuan; Shu, Xiaoming; Tao, Xincao; Zhai, Zhenguo
Abstract : Abstract: The primary aim of our case-control study was to observe delayed contrast-enhanced magnetic resonance imaging (DCE-MRI) in patients with Takayasu arteritis (TA) in comparison with magnetic resonance angiography (MRA). Twenty-seven patients including 15 with active TA and 12 with stable TA who underwent both aortic MRA and DCE-MRI were included. A total of 27 sex- and age-matched healthy volunteers were enrolled as the control group. MRA were obtained with T1WI-volume-interpolated breath-hold examination sequence or fast low-angle shot (FLASH) sequence. DCE-MRI was acquired with a free-breathing three-dimensional inversion recovery Turbo fast low-angle shot (3D IR Turbo FLASH). Neither stenosis nor delayed enhancement of arterial wall was shown in the control group. In patients with stable TA, arterial stenosis was observed on MRA. On DCE-MR, delayed enhancement of arterial walls could be observed in the active TA group but not in the stable TA group or the control group. Stenotic arteries on MRA were comparable in the active TA and stable TA (χ 2  = 2.70, P  = .259); however, delayed enhancement of arterial walls in the active-TA group were more than those in the stable group (χ 2  = 27.00, P  < .001). Our results suggest that DCE-MRI with the free-breathing 3D IR Turbo FLASH sequence could assess TA and delayed enhancement on DCE-MRI is one characteristics of the active TA.